PENERAPAN APLIKASI ACCURATE DALAM PENYUSUNAN LAPORAN KEUANGAN UKM - Khotmi, Herawati; Amrul, Rusli (Valid Jurnal Ilmiah, 2017)
Technological developments have an impact in all areas of life, including in the preparation of financial statements. Use of accounting applications in the financial statements is so important and very helpful in facilitating the operational activities of the company. The purpose of this study was to identify the accurate implementation of the operational cycle of the company at PT. Tri Utami Jaya and to analyze the application of the use of the program in the preparation of accurate financial statements.This type of research is applied research. Applied research conducted with the aim of implementing, testing and evaluating the ability of being applied in solving practical problems. The analysis technique used in this study is the System Development Life Cycle (SDLC). This study shows the use of accurate results can be applied to the company's operating cycle PT. Tri Utami Jaya. Accurate may be petrified in the recording process on any documents used at a time of recording in the form of a journal. All activities are recorded on general activity legder, cash & Bank, inventory and fixed assets that exist on accurate. The system can generate accurate financial reports quickly and accurately.